Concepts of disability in Higher Education students: Study at the University of Algarve - Leonor Borges, Maria; Helena Martins, Maria; Guerreiro, António; Pereira Leite, Lúcia [UNESP]; Luísa, Cláudia (My University, 2022)
In the national and international context, marked by the demand for the right to the inclusion of people with disabilities and the construction of an inclusive society, one of the obstacles is the attitudinal barriers sustained in excluding conceptions of disability. This study aimed to understand which are the conceptions of disability among students of Universidade do Algarve, Portugal. The findings show a disagreement with the metaphysical concept and an appreciation of the biological concept. It reveals the existence of a diversity of opinions regarding the social concept. Reflections on the implications of a higher education committed to educational inclusion and an inclusive society are presented.
Conceções de deficiência em estudantes do Ensino Superior: estudo exploratório na Universidade do Algarve
Keywords: concept; disability; EIDC scale; higher education; inclusion